The formation of a Malay child’s identity through adat, akhlak, and budi: a psychogeographical reading of Lat’s Kampung Boy (1979) - Seach Jin Beng; Jeslyn Sharnita Amarasekera (Penerbit Universiti Kebangsaan Malaysia, 2025)
The locations around us are not merely the mundane settings for our routine life stories; through meaningful interaction with the places that we are in, our thoughts, feelings, and experiences can be drastically shifted. This resonates with the psychogeographical aspect of examining people’s interaction with their surroundings that lead to personal attachments and a myriad of emotions. Lat’s Kampung Boy (1979) is an autobiographical graphic novel/comic set in the 1950s in a Malay Kampung in Perak that recounts the childhood memories of the author when growing up there. Lat’s formative years spent in his Kampung were crucial in shaping his Malay identity due to his exposure to Malay traditional rituals, culture and lifestyles. Hence, this study aims to examine how psychogeography plays a role in shaping Lat’s Malay identity as a child and adolescent through three key foundations; adat, akhlak and budi. This study argues that Lat’s experiences across distinct settings in his Kampung are essential in helping him to learn and get assimilated into the Malay identity. It highlights how Lat’s understanding of cultural values pertaining to adat, akhlak and budi was heavily impacted by his interaction and observation of his surroundings. Hence, it demonstrates that apart from the people and life experiences, places also have a significant role in shaping a child’s identity.